2017
DOI: 10.1159/000479874
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk of Hyperglycemia and Dyslipidemia in Diabetic Kidney Disease

Abstract: Background: Diabetic kidney disease (DKD) is defined by the functional, structural, and clinical abnormalities of the kidney that are caused by diabetes. Summary: One-third of both type 1 diabetes and type 2 diabetes patients suffer from DKD, which is the leading cause of end-stage renal disease, and is also associated with cardiovascular disease and high public health care costs. Serum glucose level and lipid level are key factors in the pathogenesis of DKD and are modifiable. The goal of this review is to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 91 publications
2
27
0
Order By: Relevance
“…Herein, we also confirmed that rutin treatment can reduce blood sugar in DMR rats ( Figure 2 ). Insulin resistance caused by hyperglycemia promotes the pathogenesis of hyperlipidemia, but the underlying mechanism is still unclear [ 27 ]. Figure 1 shows that STZ induces AST, ALT, ALP, CHO and TG and that rutin has beneficial effects on AST, ALP, and CHO.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we also confirmed that rutin treatment can reduce blood sugar in DMR rats ( Figure 2 ). Insulin resistance caused by hyperglycemia promotes the pathogenesis of hyperlipidemia, but the underlying mechanism is still unclear [ 27 ]. Figure 1 shows that STZ induces AST, ALT, ALP, CHO and TG and that rutin has beneficial effects on AST, ALP, and CHO.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, weight regained and improvement in metabolic indicators will further help control the development of DKD. Because high blood glucose fluctuations may damage glomerular mesangial cells and promote cell apoptosis, and lipid metabolism disorder and abnormal lipid deposition in the glomerulus may lead to proliferation of glomerular cell membrane, causing gradual accumulation of ECM, which explains the pathological basis of DKD [26].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding lipid metabolism, phosphorylated AMPK can also improve high-fat-diet-induced NASH through the suppression of several key lipogenic factors in the liver related to cholesterol and fatty acid synthesis, such as sterol regulatory element-binding protein (SREBP-1), which results in reduced triglyceride synthesis, HMG-CoAR levels, cholesterol synthesis, and ACC enzyme activation, which in turn decreases malonyl-CoA levels and reduces free fatty acids and VLDL synthesis (Musso et al, 2016;Su et al, 2017).…”
Section: Ampkmentioning
confidence: 99%
“…PPAR-α is also a transcriptional regulator of genes involved in fatty acid transport and in peroxisomal and mitochondrial βoxidation. PPAR-α phosphorylation reduces triglyceride levels by increasing lipolysis, inducing LPL to catalyze the hydrolysis of triglycerides into free fatty acids and monoacylglycerol; PPAR-α inhibits VLDL production and stimulates the production of ApoA-I and ApoA-II, which are associated with HDL (Musso et al, 2016;Pawlak et al, 2015;Su et al, 2017).…”
Section: Ppar-αmentioning
confidence: 99%